The Potential of Reflective Learning Models to Improve Students' Critical Thinking Skills - Kartika, Cindy; Hujjatusnaini, Noor; Ayatusa'adah, Ayatusa'adah (Universitas Tidar, 2022)
Improving critical thinking skills is an important skill that needs to be developed in the 21st century which has the main goal of achieving science education. Critical thinking skills can be developed through ongoing training for students during the learning process. This study aims to see the potential of the Reflective learning model for improving students' critical thinking skills by using the Quasi-experimental method with the Pretest-Posttest control group design. The research subjects were 30 students in class VIII odd semester 2021/2022 at SMPN 12 Palangka Raya. The ability of students' critical thinking skills experienced a significant increase where students obtained an average score of 25.33%. The conclusion that can be drawn based on the analysis of research data states that the increase in students' critical thinking skills in science learning, especially in the material of the human digestive system by using reflective learning models, has experienced a significant increase. The reflective learning model has the potential to improve students' critical thinking skills.